Confronting a Christian Neighbor: Sudanese Representations of Ethiopia in the Early Mahdist Period, 1885-89 - (:unkn) unknown (My University, 2009)
This article deals with the Sudanese-Ethiopian conflict (1885-1889) from a Mahdist perspective, in the wider context of the European scramble for Africa. Focusing on Sudanese representations of Ethiopia as well as on the causes underlying the conflict, we confront a Mahdist chronicle of particular historiographical significance with a range of historical sources. Departing from a purely jihadist framework of analysis, we highlight various Mahdist conceptualizations of Christian Ethiopia as well as historical, political, military and economic processes conducive to the outbreak of an armed confrontation between the two independent African states. The paper argues that the Sudanese ruling elite resorted to jihadist discourse as a legitimizing device rather than as an inflexible policy, and examines more specific rhetoric instruments meant to justify Mahdist attitudes towards the Christian kingdom. Whereas prophetical visions were used to make the Khalifa's Ethiopian policy acceptable to Mahdist eyes, the ambivalent legacy of early Muslim-Aksumite contacts was reactivated in the framework of a dialogue with the Ethiopian enemy.
Keywords: African Research